The end of the "grand narrative"? - Nagode, Aleš (Muzikološki zbornik, 2013)
Observation of the late 19th and early 20th century religious music in Slovenia was so far incorporated into different historiographical grand narratives.These attempts have in general led to selective use and distortion of information about historical reality. It seems that the only feasible method left is the micro-historical observation.
Keywords: 19.-20.st.; cerkvena glasba; glasbeno zgodovinopisje; Slovenia; Slovenija